New Advances in the Management of Refractory Angina Pectoris - Cheng, Kevin (Eur Cardiol, 2018)
Refractory angina is a significant clinical problem and its successful management is often extremely challenging. Defined as chronic angina-type chest pain in the presence of myocardial ischaemia that persists despite optimal medical, interventional and surgical treatment, current therapies are limited and new approaches to treatment are needed. With an ageing population and increased survival from coronary artery disease, clinicians will increasingly encounter this complex condition in routine clinical practice. Novel therapies to target myocardial ischaemia in patients with refractory angina are at the forefront of research and in this review we discuss those in clinical translation and assess the evidence behind their efficacy.